(untitled) (Journal of Academic Research, 2022)
This study focuses on E-learning technologies that have the potential to facilitate teaching and learning strategies by using the different computer tools. Nowadays, the applications of E-Learning become the most applicable in all levels of education, and this is owing to the widespread of the COVID-19 pandemic. The trends of E-learning prevails the new form of foundations for future direction and development for educational and training purposes. The trends to the learning process can be blended learning, micro learning, gamification, personalized learning, and Massive Open Online Courses. This study aims to investigate the E-learning concept; to highlight advantage and disadvantage of E-learning; to find out the important aspects of E-learning, and how to implement this technology in the education system in order to improve the educational level and reach the desired outcomes. The findings of this study reveal that Blended learning is the most effective and convenient for implementation. Moreover, E-learning has benefits because it has the potential to move from traditional learning to e-learning, especially in applied sciences.